The Dynamics of Political Participation and Governance in Gombe State, Nigeria - Adeleke, Odekunle kehinde; Garafini, Abdulsabur Adamu; Eikojonwa, Oyebade Hannah (Kashere Journal of Politics and International Relations, 2025)
This study examines the dynamics of political participation, electoral processes, civic engagement, and policy implementation in Gombe State, Nigeria, between 2015 and 2023. The focus is on understanding how electoral processes and civic engagement shaped governance outcomes in the region. A sample of 400 respondents, selected through stratified sampling, provided data via structured questionnaires. Using both qualitative and quantitative analyses, the study reveals significant relationships between political participation and policy outcomes. The results suggest that increased civic engagement has influenced governance effectiveness in Gombe State, with key implications for future elections and policy reforms.